Tubeless percutaneous nephrolithotomy versus standart nephrolithotomy in geriatric patients: Single surgeon experience (Annals of Medical Research, 2021)
Aim: Percutaneous nephrolithotomy(PCNL) is the most effective and reliable surgical procedure in the world fob large renal stones.Tubeless PCNL(T-PCNL) has recently been used effectively.The aim of our study is to compare two methods in elderly patients who underwent T-PCNL and Standart PCNL(S-PCNL).Material and Methods: Our study included 60 patients over 60 years of age who underwent operation for renal stones in Beylikduzu State Hospital.T-PCNL was performed on 30 of these patients,whereas S-PCNL was performed on the remaining 30 patients.The mean age, presence of hypertension and diabetes,body-mass index(BMI) and stone size information was recorded within the framework of demographic data of the patients.Length of intraoperative and postoperative hospital stays, operation times,stone free rates,requirement of preoperative blood transfusion,decrease in postoperative hemoglobin,decrease in postoperative parenchymal thickness and Clavien scores were reviewed.Chi-square test and Student T Test was used for statistical analysis.Results: In the light of the intraoperative and postoperative data,a statistically significant difference was found in favor of T-PCNL group compared to the S-PCNL group,in terms of length of hospital stays,operation times and postoperative narcotic analgesic use (p 0.05).On the other hand,no statistically significant difference was found between the two groups on the basis of the stone free ratio,Clavien scoring, preoperative blood transfusion and postoperative renal parenchymal thickness.Conclusion: T-PCNL is a safe and effective surgical procedure in geriatric patients with large renal stones,as is S-PCNL.T-PCNL was found to be superior in terms of length of hospital stay, operation times and postoperative narcotic analgesic use.